Private Investment in Transport Returns to Pre-Crisis Levels in 2010 - Jett, Alexander (World Bank, Washington, DC, 2012)
In 2010, 93 transport projects with private participation reached financial or contractual closure in 16 low- and middle-income countries, involving investment commitments (hereafter investments) of US$28.3 billion.1 In addition, transport projects implemented in 1990-2009 attracted new investment of US$0.7 billion, bringing total investment in transport to US$29 billion in 2010. Investment in 2010 increased by 40 percent compared with 2009, bringing investment back to pre-crisis levels. By number of projects, activity in 2010 grew by 75 percent compared with 2009. Private activity was concentrated in India and road projects globally. India alone accounted for 56 percent of investment and 61 percent of new projects, driving most of the growth in activity in 2010. Road projects accounted for 69 new projects and US$20 billion of investment, the highest level thus far thanks to activity in India. In addition, there were sixteen port projects with investment of US$3.7 billion, two railway projects with investments of US$3 billion, and six airport projects with investments of US$2.3 billion.